Drivers of changing supply chain capability expectations in the online retail sector: the role of sales transactions. - Alexander, Paul (Purchasing Management Association of Canada, 2010)
Online retailers have created new demands and opportunities for their supply chain providers. This paper reports on a five year UK-based study of this market space, whose logistics needs are in part provided by third party e-fulfilment organisations (3PEFs), businesses offering traditional and innovative services specifically to online retailers. To establish links between 3PEF capabilities and online retailer needs, the Croom e-Business Maturity Model is used to map core 3PEF capabilities and in this way link 3PEF offerings to supply chain needs of theircustomers. Over the five years of the study, it is observed that a significant trigger for developing new capabilities is embedded in sales transactions. A model is presented to explain how customer expectations are transformed in these same sales transactions, and application of this model in a wider logistics context is also suggested.